2000
DOI: 10.1108/02656710010304573
|View full text |Cite
|
Sign up to set email alerts
|

Total quality management, ISO 9000 certification and performance improvement

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
1
19

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(175 citation statements)
references
References 12 publications
10
145
1
19
Order By: Relevance
“…In general, the results of this study indicated that ISO 9000 certification has no effect on the quality practices, and hence LR level, of European pharmaceutical manufacturers. This is in line with findings of Al-Najem et al (2013), Sun (2000), Williams (1997) and Taylor (1995), who claimed that ISO 9000 does not serve as a platform for quality excellence programmes such as LM and TQM. Indeed, as Al-Najem et al (2013) discovered for the case of Kuwaiti SMEs, ISO 9000 only contributes to the training of the workforce and managers.…”
Section: H3: Iso 9000 Certified Pharmaceutical Firms Differ Significasupporting
confidence: 90%
See 1 more Smart Citation
“…In general, the results of this study indicated that ISO 9000 certification has no effect on the quality practices, and hence LR level, of European pharmaceutical manufacturers. This is in line with findings of Al-Najem et al (2013), Sun (2000), Williams (1997) and Taylor (1995), who claimed that ISO 9000 does not serve as a platform for quality excellence programmes such as LM and TQM. Indeed, as Al-Najem et al (2013) discovered for the case of Kuwaiti SMEs, ISO 9000 only contributes to the training of the workforce and managers.…”
Section: H3: Iso 9000 Certified Pharmaceutical Firms Differ Significasupporting
confidence: 90%
“…Gotzamani and Tsiotras, 2001;Magd, 2006;Escanciano et al, 2001). However, an opposite view is suggested by Sun (2000), who comments that ISO 9000 offers a limited platform to support the implementation of TQM and LM. As far as the pharmaceutical sector is concerned, a relatively low level of ISO 9000 certification has been observed when compared to other industries (Freitas, 2009).…”
Section: Iso Contribution To Lean Manufacturing Implementationmentioning
confidence: 99%
“…General and managerial benefits have also been stressed: financial performance, leadership in quality issues, motivation, training and awareness, communication, work climate, etc. Second, the literature has focused on the external impacts of ISO 9001: customer satisfaction and service, complaint reduction, delivery, supplier relations, image, sales, market share, etc (Sun, 2000;Escanciano et al, 2001;Standards Council of Canada, 2000). Although critical approaches toward ISO 9001 are relatively scarce in the literature, certain studies have questioned the standard benefits or stressed the various pitfalls associated with its implementation (Quazi et al, 2002;Moatazed-Keivani et al, 1999).…”
Section: The Controversial Impact Of Iso Certificationmentioning
confidence: 99%
“…Although certain studies offer general recommendations to managers, they are most often based on statistical results and not on firsthand experience of the standard. As a result, these recommendations to managers tend to remain rather oblique: incorporation of ISO certification with the philosophy of total quality management, establishment of key performance indicators, involvement of stakeholders in ISO design, development of best practices and manufacturing excellence through certification, use of ISO as a catalyst for change, consideration of the connection between ISO implementation and supply chain management, monitoring of ISO implementation by suppliers, etc (Gonzáles-Benito and Gonzáles-Benito, 2008;Naveh and Marcus, 2005;Delmas, 2001;Sun, 2000;Christmann and Taylor, 2006).…”
Section: The Controversial Impact Of Iso Certificationmentioning
confidence: 99%
“…In addition, as numerous studies show (among others, Buttle, 1997;Brown et al, 1998;Neergaard, 1999;Sun, 2000;Escanciano et al, 2001), the level of satisfaction with the implementation of ISO 9001 is very closely linked to the level of positive effects obtained as a result of this standard, to an extent that the stronger these positive effects appear to be, the greater the level of satisfaction with implementation. For this reason, we shall analyse prior studies on the acquisition of these positive effects and to what extent the determining factors that will be the object of analysis in this research have influenced them.…”
Section: Level Of Satisfaction and The Positive Effects Of Implementimentioning
confidence: 95%